Substituent tuning of Cu coordination polymers enables carbon-efficient CO2 electroreduction to multi-carbon products - Huiying Deng; Tingting Liu; Wenshan Zhao; Jundong Wang; Yuesheng Zhang; Shuzhen Zhang; Yu Yang; Chao Yang; Wenzhi Teng; Zhuo Chen; Gengfeng Zheng; Fengwang Li; et al. (Nature Communications)
Abstract CO2 electroreduction is a potential pathway to achieve net-zero emissions in the chemical industry. Yet, CO2 loss, resulting from (bi)carbonate formation, renders the process energy-intensive. Acidic environments can address the issue but at the expense of compromised product Faradaic efficiencies (FEs), particularly for multi-carbon (C2+) products, as rapid diffusion and migration of protons (H+) favors competing H2 and CO production. Here, we present a strategy of tuning the 2-position substituent length on benzimidazole (BIM)-based copper (Cu) coordination polymer (CuCP) precatalyst – to enhance CO2 reduction to C2+ products in acidic environments. Lengthening the substituent from H to nonyl enhances H+ diffusion retardation and decreases Cu-Cu coordination numbers (CNs), favoring further reduction of CO. This leads to a nearly 24× enhancement of selectivity towards CO hydrogenation and C-C coupling at 60 mA cm−2. We report the highest C2+ product FE of more than 70% at 260 mA cm−2 on pentyl-CuCP and demonstrate a CO2-to-C2+ single-pass conversion (SPC) of ~54% at 180 mA cm−2 using pentyl-CuCP in zero-gap electrolyzers.